2020
DOI: 10.11113/sh.v12n3.1744
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review:Online Social Media Interaction in Education and Employment Cluster/ Tinjauan Literatur Sistematik: Interaksi Media Sosial Atas Talian dalam Kluster Pendidikan dan Pekerjaan

Abstract: The research is related to online social media interactions in education and employment clusters. The researcher has developed five objectives of the study specifically to identifying the top forms of social media in Malaysia, to identifying the tendency of Malaysians to habit social media, to identifying online interaction platforms in the employment sector, to identifying the effectiveness of social media in generating income and for educational purposes. All objectives use two methods of analysis that is cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Therefore, it is necessary to address the improvement of graduates' competency to make sure they match the current and future labour market needs. In this instance, the studies by Saleh and Rosli (2020) and Pereira et al (2020) suggested a strategy for enhancing graduate employability by meeting the demands of the industry and focusing on work-life competency and the key skills needed for the advancement of the organisation. Meeting the demands of the labour market requires a transformation of Higher Education Institutions (HEIs) by considering the perspectives of several interest groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, it is necessary to address the improvement of graduates' competency to make sure they match the current and future labour market needs. In this instance, the studies by Saleh and Rosli (2020) and Pereira et al (2020) suggested a strategy for enhancing graduate employability by meeting the demands of the industry and focusing on work-life competency and the key skills needed for the advancement of the organisation. Meeting the demands of the labour market requires a transformation of Higher Education Institutions (HEIs) by considering the perspectives of several interest groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, all of these terms refer to learning methods that will take place in a variety of situations, regardless of location, through the use of the internet. If internet access is limited, having a computer alone is insufficient (Saleh & Rosli, 2020). As a result, using the internet in the educational process is now a requirement, not an option.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that the only way to communicate is through the use of information technology. According to (Saleh & Rosli, 2020), communication through online is increasingly important, especially during MCO in Malaysia. There are several studies related to online shopping behaviour that have been conducted in several countries.…”
Section: Introductionmentioning
confidence: 99%